2020
DOI: 10.3390/ijms21165680
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Nitric Oxide to AHR-Ligand-Mediated Keratinocyte Differentiation

Abstract: Activation of the aryl hydrocarbon receptor (AHR) in normal human epidermal keratinocytes (NHEKs) accelerates keratinocyte terminal differentiation through metabolic reprogramming and reactive oxygen species (ROS) production. Of the three NOS isoforms, NOS3 is significantly increased at both the RNA and protein levels by exposure to the very potent and selective ligand of the AHR, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Inhibition of NOS with the chemical N-nitro-l-arginine methyl ester (l-NAME) reversed T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…TCDD is known to activate the EGFR-ERK pathway and accelerate epithelial differentiation (Hansen et al, 1997, Sibilia and Wagner, 1995, Sutter et al, 2011, Kennedy et al, 2013, Sutter et al, 2020, Sutter et al, 2023, Fernandez-Salguero et al, 1996, Puga et al, 2005, Choi et al, 2006, Patel et al, 2006), an effect that may lead to promotion of precocious eyelid opening in postpartum pups (Theobald and Peterson, 1997, Gray et al, 1997, Miettinen et al, 2004, Dominey et al, 1993) and development of chloracne, a hyperkeratotic skin disorder, found in humans exposed to high dose TCDD (Sutter et al, 2011, Muenyi et al, 2014, Loertscher et al, 2001). This effect of TCDD, however, is insufficient to block embryonic lid closure.…”
Section: Discussionmentioning
confidence: 99%
“…TCDD is known to activate the EGFR-ERK pathway and accelerate epithelial differentiation (Hansen et al, 1997, Sibilia and Wagner, 1995, Sutter et al, 2011, Kennedy et al, 2013, Sutter et al, 2020, Sutter et al, 2023, Fernandez-Salguero et al, 1996, Puga et al, 2005, Choi et al, 2006, Patel et al, 2006), an effect that may lead to promotion of precocious eyelid opening in postpartum pups (Theobald and Peterson, 1997, Gray et al, 1997, Miettinen et al, 2004, Dominey et al, 1993) and development of chloracne, a hyperkeratotic skin disorder, found in humans exposed to high dose TCDD (Sutter et al, 2011, Muenyi et al, 2014, Loertscher et al, 2001). This effect of TCDD, however, is insufficient to block embryonic lid closure.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signal is required for embryonic eyelid closure, as both the germline and OSE-specific Egfr KO cause basal epithelial cell hypoproliferation and a fully penetrable EOB defect ( 49 , 81 , 82 ). By activating the EGFR pathway, TCDD is shown to reduce the EOB phenotype of Egfr −/− pups by 50%, presumably through inducing ligands that activate other receptors of EGFR family to promote lid closure ( 83 , 84 ), and to promote precocious eyelid opening in postpartum pups through accelerating epithelial differentiation ( 85 , 86 , 87 ). Our data suggest that TCDD-induced EGFR activation is moderate and by itself is insufficient to alter the eyelid closure programs, because all TCDD-treated WT pups have normal lid closure ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The function of NO on skin health is controversial. The expression levels of NOS3 and NO production have been reported to be necessary for aryl hydrocarbon receptor-ligand-mediated keratinocyte differentiation [ 27 ]. In the macrophage, NO is required to possess antibacterial activity for the immune system [ 26 ].…”
Section: Discussionmentioning
confidence: 99%